Regulation of influenza A virus mRNA splicing by CLK1 - Artarini, A; Meyer, M; Shin, Y; Huber, K; Hilz, N; Bracher, F; Eros, D; Orfi, L; Keri, G; Goedert, S; Neuenschwander, M; Von Kries, J; et al. (Elsevier, 2019)
Influenza A virus carries eight negative single-stranded RNAs and uses spliced mRNAs to increase the number of proteins produced from them. Several genome-wide screens for essential host factors for influenza A virus replication revealed a necessity for splicing and splicing-related factors, including Cdc-like kinase 1 (CLK1). This CLK family kinase plays a role in alternative splicing regulation through phosphorylation of serine-arginine rich (SR) proteins. To examine the influence that modulation of splicing regulation has on influenza infection, we analyzed the effect of CLK1 knockdown and inhibition. CLK1 knockdown in A549 cells reduced influenza A/WSN/33 virus replication and increased the level of splicing of segment 7, which encodes the viral M1 and M2 proteins. CLK1-/- mice infected with influenza A/England/195/2009 (H1N1pdm09) virus supported lower levels of virus replication than wild-type mice. Screening of newly developed CLK inhibitors revealed several compounds that have an effect on the level of splicing of influenza A gene segment M in different models and decrease influenza A/WSN/33 virus replication in A549 cells. The promising inhibitor KH-CB19, an indole-based enaminonitrile with unique binding mode for CLK1, and its even more selective analogue NIH39 showed high specificity towards CLK1 and had a similar effect on influenza mRNA splicing regulation. Taken together, our findings indicate that targeting host factors that regulate splicing of influenza mRNAs may represent a novel therapeutic approach.